Exploring Teacher’s Use of Deductive and Inductive Methods and The Teaching of English Text Types - Saifuddin, Muhammad; Charisma Rahayu (Universitas Nahdatul Ulama Surabaya, 2024)
Deductive and Inductive method are two common teaching method applied by teachers. Both of the methods provide advantages to teachers to their teaching process. However, each of them also present different principles of the implementation. In that case, this research was carried out to figure out the teacher’s teaching activities representing the principles of implementing deductive and inductive method as well as to figure out the teacher’s reasons of selection the teaching methods (deductive or inductive method) in context of teaching English text types. To obtain the data to answer the research questions, a case study approach was used. The instruments used were observation and interview while the participant of this study was the English teacher of one of vocational school in Jombang having 10 years experiences. The findings of the research showed that the teacher applied different method for different class as it appeared in teacher’s selection of the activities representing the principles of teaching methods. The teacher selected to apply deductive method in which the activities presented the general rule – example – practice. Meanwhile, in inductive teaching method, the activities covered example – practice – general rule. In addition, it was also revealed that the teacher considered students’ level of interaction, text type, vocabulary usage as the reasons of selection between deductive or inductive method. At last, deductive and inductive method were said to be effective and appropriate teaching method which provided students to learn deductively and inductively as long as the teacher choose the method appropriately based on some considerations; interaction level, text type, and vocabulary usage. These research results contribute significantly to the teachers who often find difficulties which way best to apply when teaching English text types since they present different genre of text and the language use. Thus, this research results present the practical ways as high consideration to those teachers who are willing to undergo the methods whether it is deductive or inductive teaching method.